2011
DOI: 10.1080/19371918.2011.579499
|View full text |Cite
|
Sign up to set email alerts
|

Autism and the African American Community

Abstract: It is estimated that autism spectrum disorders (ASD) affect 1 in 500 live births per year. However, due to varying techniques for diagnosis and treatment, the disability remains the subject of debate. African Americans tend to suffer disproportionate rates of disability and disease when compared to other racial and ethnic groups due to access to preventative and curative care. However, evidence demonstrates that although rates of diagnosis for autism occur at the same rates in all racial groups, diagnosis in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Although we adjusted for family-level education, residual differences in socioeconomic resources between black and white children likely exist, contributing to the differential changes over time. Previous research has noted under-diagnoses of mental illnesses such as autism for black and other minority children compared to white children (Gourdine, Baffour, & Teasley, 2011). There has also been speculation that minority children are under-screened for autism spectrum disorders (ASD) by health professionals, which is possibly the result of statistical discrimination (Balsa & McGuire, 2001; Gibson, 2007; Mandell, Listerud, Levy, & Pinto-Martin, 2002; Mandell, Listerud, Levy, & Pinto-Martin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although we adjusted for family-level education, residual differences in socioeconomic resources between black and white children likely exist, contributing to the differential changes over time. Previous research has noted under-diagnoses of mental illnesses such as autism for black and other minority children compared to white children (Gourdine, Baffour, & Teasley, 2011). There has also been speculation that minority children are under-screened for autism spectrum disorders (ASD) by health professionals, which is possibly the result of statistical discrimination (Balsa & McGuire, 2001; Gibson, 2007; Mandell, Listerud, Levy, & Pinto-Martin, 2002; Mandell, Listerud, Levy, & Pinto-Martin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Some challenges faced by CLD families include limited knowledge of speech-language and audiology services, difficulty accessing the internet, delay in referrals, and delay in finding service providers [54]. In addition, several CLD families have limited understanding of health insurance and policies [55], receive late identification and diagnosis [56], and face financial barriers to accessing services [57]. Some families have limited understanding of assessments and their purpose [32].…”
Section: Implications For Cliniciansmentioning
confidence: 99%
“…Multiple studies have identified faith as a prominent support mechanism for parents raising a child with ASD (Bayat, 2007;Tarakeshwar & Pargament, 2001). For instance, spirituality was highlighted as a hallmark of how African American parents make sense of their role as a parent of a child with special needs (Gourdine, Baffour, & Teasley, 2011). Likewise, other authors have identified spiritual faith and expression as features of the parenting experience for parents of children with ASD in a multitude of multicultural contexts (Dyches, Wilder, Sudweeks, Obiakor, & Algozzine, 2004;Mandell & Novak, 2005).…”
Section: The Factors That Influence Family Decision Making About Asd mentioning
confidence: 99%